Nutritive value of meat and bone meal for growing pigs - Partanen, Kirsi; Näsi, Matti (Agricultural and Food Science, 1994)
Six barrows, with an average initial body weight of 88 kg, were used in a digestibility and balance experiment to study the nutritive value of meat and bone meal (MBM). The MBM, which contained 478 g crude protein and 322 g ash/kg dry matter (DM), was included in barley-based diets at two levels: 100 and 200 g/kg. The experiment was conducted according to a two-period reversal design. The apparent digestibilities of organic matter, crude protein and crude fat in the MBM were 0.910, 0.909 and 0.730, respectively. The MBM was calculated to contain 434 g digestible crude protein, 14.26 MJ metabolizable energy and 8.82 MJ net energy/kg DM. The efficiency of nitrogen utilization decreased with an increasing MBM supply. Due to relatively high mineral intakes, the apparent digestibilities of calcium and phosphorus remained low.